Systemic sclerosis phase III clinical trials: Hope on the horizon?. Issue 3 (October 2018) - Aringer, Martin; Denton, Christopher P
While significant progress has been made in treating systemic sclerosis, many patients still have an outcome that is far from satisfactory. For the first time in history, several drugs are now in phase III randomized controlled trials. Approaches tested include the anti-B cell antibody rituximab, the anti-interleukin-6 receptor antibody tocilizumab, the antifibrotic drugs nintedanib and pirfenidone, and the cannabinoid receptor mimetic lenabasum. That all these drugs are in advanced clinical trials despite the relatively low incidence of the disease therefore is good news. Not only is there realistic hope that at least some of the approaches will work, this also indicates growing industry interest, for most of the trials are company-sponsored. This review attempts to delineate the ongoing trials and to summarize the underlying evidence of these candidate systemic sclerosis drugs.